BANJARESE ISLAMIC SCHOLARS (‘ULEMA) AND SOCIAL TRANSFORMATION IN TEMBILAHAN (PRELIMINARY RESEARCH) - Raihani Raihani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Banjarese, an ethnic group in South Kalimantan, were estimated to have migrated to Tembilahanand its surroundings in the 19th century following the defeat of the Banjar Sultanate bythe Dutch colonialists. The religious intellectualism rooted in the Banjarese tradition has untilnow resulted in the production of ‘ulema (religious scholars) even in new places to which theyhave migrated. Using in-depth interviews with several figures in Tembilahan, this preliminarystudy sheds light on how Banjarese ‘ulema in the area have contributed to the transformationof society. This study is important as there has not been solid research-based informationabout this important topic publicly available. It found that Banjarese ‘ulema have played animportant role in educating people through formal and informal ways to be religiously committedand socio-economically active. They have demonstrated dynamic relations with society, butsome of them were not immune from political and material temptations. It seems that the fartherthey stay away from such temptations, the more charisma they develop, and the more the opportunities they may have to contribute to the social transformation of Tembilahan society